2010
DOI: 10.1111/j.1469-8137.2010.03331.x
|View full text |Cite
|
Sign up to set email alerts
|

A putative TRAPPII tethering factor is required for cell plate assembly during cytokinesis in Arabidopsis

Abstract: Summary At the end of the cell cycle, the plant cell wall is deposited within a membrane compartment referred to as the cell plate. Little is known about the biogenesis of this transient membrane compartment. We have positionally cloned and characterized a novel Arabidopsis gene, CLUB, identified by mutation. CLUB/AtTRS130 encodes a putative TRAPPII tethering factor. club mutants are seedling‐lethal and have a canonical cytokinesis‐defective phenotype, characterized by the appearance of bi‐ or multinucleate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 71 publications
(192 reference statements)
2
46
1
Order By: Relevance
“…Colocalization at the TGN and functional studies suggest that TRAPPII acts as a GEF for RABA1c, facilitating RABA1c-mediated trafficking of material from the TGN to the cell plate (Qi et al, 2011). Mutants of the TRAPPII subunit, AtTRS130, exhibit severe cytokinesis defects and irregular aggregations of RABA1c around cell plate-like structures (Jaber et al, 2010;Qi et al, 2011). The expression of constitutively active RABA1c partially rescues attrs130 (Qi et al, 2011), supporting the role of AtTRS130 upstream of RABA1c.…”
Section: Tgn and The Cell Plate: A Timely Connectionmentioning
confidence: 89%
“…Colocalization at the TGN and functional studies suggest that TRAPPII acts as a GEF for RABA1c, facilitating RABA1c-mediated trafficking of material from the TGN to the cell plate (Qi et al, 2011). Mutants of the TRAPPII subunit, AtTRS130, exhibit severe cytokinesis defects and irregular aggregations of RABA1c around cell plate-like structures (Jaber et al, 2010;Qi et al, 2011). The expression of constitutively active RABA1c partially rescues attrs130 (Qi et al, 2011), supporting the role of AtTRS130 upstream of RABA1c.…”
Section: Tgn and The Cell Plate: A Timely Connectionmentioning
confidence: 89%
“…An insertion mutant in the TRAPPII gene Trs130 was found to be allelic to club-1 (Sö llner et al, 2002); therefore, we named it trs130/club-2. club mutants, which were identified as being cytokinesis defective in a forward genetic screen, are described elsewhere (Jaber et al, 2010). In this study, we characterize the Arabidopsis Trs120 ortholog (AtTRS120).…”
Section: Screening Insertion Mutants In Arabidopsis Tethering Factorsmentioning
confidence: 99%
“…5b, c), similar to vesicles frequently associated with the nascent cell plate in freshly divided cells. However, it is interesting to note that none of the cells with protuberances were enlarged or were multi-nucleated, the typical morphological characteristics of cytokinesis mutants (Jaber et al 2010). It looked as if the protuberances occurred randomly as a misdirected layering of cell wall material on the inner surface of the existing primary cell wall.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, cell wall defects were found only in cells with a single nucleus which was predominantly in interphase. In many cytokinesis mutants, the reported cell wall stubs were situated in the equatorial division plane attached to the parental wall at opposite ends, sometimes leaving a gap in the middle, suggesting that cell plate formation, expansion, or maturation, had failed at some point (Assaad et al 1996;Jaber et al 2010;Lukowitz et al 1996). In contrast, cell wall ingrowths in sac9 cells arose at random sites from the preexisting wall growing towards the center of the cell, but not restricted to the position of a future cell plate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation